Nilai-Nilai Pendidikan Kewarganegaraan Dalam Kitab al Ahkam al Sulthaniyah - muhammad syamsul huda (Universitas KH. A. Wahab Hasbullah, 2019)
In Islamic turost there are works in the field of political science which is still being discussed, namely al-Ahkam al-Sultania w'al-Wilayat al-Diniyya. Al-Mawardi's main work in the political field. In the book there is an explanation of the rights and obligations of citizens which is one of the main topics in Citizenship Education. This education emerged from the concept of citizenship which in the modern era was considered important for the strengthening of a country. The problems that the author examines in this study, namely: What are the contents of the values ​​of citizenship education in the book of Ahkam al-Sulthaniyah? What is the relevance to the 18 values ​​of cultural and national character education proposed by the Ministry of National Education in 2010? Thus, based on the results of this study it is known that in every work of Islamic turots there are some content values ​​that are still relevant despite being long-lived. Although some have to be re-interpreted with the current context. From the results of this study the authors found 20 values ​​of citizenship education in the book that are relevant to the 11 values ​​of national character put forward by the Ministry of National Education in 2010.